Reproductive modes of Atlantic forest hylid frogs: A general overview and the description of a new mode - Haddad, CFB; Sawaya, R. J. (Wiley-Blackwell, 2000)
This paper reports a new reproductive mode in anurans, observed for the green treefrog, Hyla leucopygia, a species from the Atlantic Forest of Brazil and a member of the H. albosignata group. The reproductive mode of H. leucopygia is defined as follows: aquatic eggs and embryos in subterranean constructed nests; subsequent to flooding, feeding tadpoles in ponds or streams. We suggest that the new reproductive mode is widespread among the species in the H. albosignata group. The specialized courtship behaviors of H. leucopygia, characterized by vocalizations and a stereotyped sequence of mutual touches between male and female, are described. A review of the reproductive modes of hylid frogs is provided, with 11 modes recognized for the Atlantic Forest hylids and 12 modes For hylids around the world.
Keywords: Anura; Atlantic Forest; Hyla leucopygia; Hylidae; new reproductive mode; reproductive behavior; subterranean nest